The study of antiviral drugs targeting SARS-CoV-2 nucleocapsid and spike proteins through large-scale compound repurposing - Xuqiao Hu; Zhenru Zhou; Fei Li; Yang Xiao; Zhaoyang Wang; Jinfeng Xu; Fajin Dong; Hairong Zheng; Rongmin Yu (Heliyon, 2021)
Contributing to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) clinical treatment, a drug library encompassing approximately 3,142 clinical-stage or FDA-approved small molecules is profiled to identify the candidate therapeutic inhibitors targeting nucleocapsid protein (N) and spike protein (S) of SARS-CoV-2.16 screened candidates with higher binding affinity are evaluated via virtual screening. Comparing to those under trial/temporarily used antivirus drugs (i.e., umifenovir, lopinavir), ceftriaxone, cefotaxime, and cefuroxime show higher binding affinities to the N-terminal domain of N protein (N-NTD), C-terminal domain of N protein (N-CTD), and receptor-binding domain of S protein (S-RBD). Cefotaxime and cefuroxime have high binding affinities towards S-RBD with angiotensin-converting enzyme 2 (ACE2) complex via influence the critical interface sites at the interface of S-RBD (Arg403, Tyr453, Trp495, Gly496, Phe497, Asn501and Tyr505) and ACE2 (Asn33, His34, Glu37, Asp38, Lys353, Ala386, Ala387, Gln388, Pro389, Phe390 and Arg393) complex.